PERSPEKTIF HAK ASASI MANUSIA TERHADAP PERKAWINAN BEDA AGAMA DI INDONESIA - Mauliani, Siti Mauliani; Wijayanti, Septi Nur (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Interfaith marriage has become a phenomenon that presents debate in community groups, according to the law interfaith marriage is not a valid marriage, it is regulated in the constitution. Therefore, this writing specifically focuses on how the human rights perspective views the phenomenon of the prohibition of approval of interfaith marriage, then aims to be a comprehensive study related to the mechanism of implementing human rights in the policy of prohibiting interfaith marriage. The prohibition of interfaith marriage is not a form of violation of the constitution but rather a form of the state exercising its authority, namely the Limitation of Human Rights.